RISK FACTORS FOR THE OCCURRENCE OF POSTOPERATIVE DELIRIUM - Jovanović, Vesna; Ladjević, Nebojša; Šipetić Grujičić, Sandra (HEALTH CARE, 2023)
The occurrence of postoperative delirium (POD) has been recognized in recent decades as an important clinical syndrome, especially in elderly patients undergoing surgical treatment. The aim of this review was to examine the preoperative, intraoperative and postoperative factors that can lead to the occurrence of POD. The risk factors for developing POD are numerous, and most importantly, many can be modified. Some of the most significant risk factors for the occurrence of POD are older age, alcohol abuse, preoperatively worse functional and cognitive status, presence of depression and dementia. A higher incidence of POD was observed in patients undergoing more complex surgical procedures such as cardiac, vascular and orthopedic hip fracture operations. It was observed that after emergency surgical procedures POD occurs 1.5 to 3 times more often than during elective planned surgical procedures. Also, intraoperative bleeding and the application of transfusion were identified as significant risk factors for the occurrence of POD. In order to avoid cognitive deficits caused by longer exposure to anesthesia, research has shown that anesthetic titration by monitoring the bispectral index, as well as evoked auditory potentials, can reduce excessive exposure to anesthetics and thus reduce the risk of postoperative cognitive dysfunction. Knowledge of risk factors and identification of patients at increased risk are the basis of a strategy for the prevention of this syndrome. Current evidence suggests that perioperative avoidance of benzodiazepine use as well as adequate perioperative pain control are key measures to reduce the risk of POD